Art and Transport: Background Music at The Train Stations in Java Island, Indonesia - Rahmawati, Ainun; Dewanti, Dewanti; Parikesit, Danang; Timms, Paul; Barnard, Yvonne (Universitas Ibn Khaldun Bogor, 2024)
Nowadays, music plays an essential role in train stations. Many train stations offer music in various forms. This study focuses on the background music, defined as music prepared and recorded in advance by the train station manager and played at certain times with a specific duration in the stations. The songs or musical instruments played in Java Island, Indonesia, are folk songs that reflect the identity of each region. The objectives of the study are to analyse the background music selection in the train station globally, to identify the purpose of background music used in the train stations from the railway company perspective, to identify the criteria and characteristics of folk songs used as background music, and to analyse the passengers’ perspective on background music at the train station. The research utilised a qualitative case study research methodology. The methods used include online research and literature reviews to answer the first objective regarding background music selection at train stations globally. Then in-depth interviews with rail service providers and the rail service users. The conclusions obtained are: 1) the Japan Railway Company create unique melodies for each line and station to help the train passengers remember specific locations and lines and guide the passengers to steps and orderly queues during peak hours; 2) KAI's purpose in playing background music at the station is for additional services for passengers as well as a sign that the train has arrived and to provide a regional identity as one of the local cultures; 3) the percentage of background music is dominated by instrumentals with traditional arrangements; 4) About 80% of the respondents who were interviewed said that the songs played at the station had a place for bonding with the location, others are nostalgic, proud, peaceful and relaxed.